Edukasi Manajemen Nyeri Knee Osteoarthritis (KOA) pada Komunitas Lansia Sidoluhur, Kabupaten Malang - Dinda Camela Damayanti; Faiqatul Qari’ah; Abdul Rahmat Amin Mayu; Adam Samudra Huamaidy; Achmad Banu Mustofa; Raymond Oscar; Nadya Styarini Farizka; Bayu Prastowo (Rena Cipta Mandiri, 2024)
Knee Osteoarthritis (KOA) is a type of rheumatic disease of the knee that is most commonly experienced by the elderly due to metabolic disorders. Some risk factors for KOA include age, obesity, and physical activity. It is important for the community, especially the elderly with the majority of jobs as farmers, to understand KOA pain management. Community service aims to provide education on KOA pain management. This service method uses a Service Learning (SL) approach with 22 participants with indications of KOA. Indicators of service achievement using pre-test and post-test with indicators including definitions, signs and symptoms, risk factors, and rehabilitation. The results of the service showed an increase in knowledge from 17% to 86%. So that KOA pain management education in the Sidoluhur elderly community is significantly able to increase participant knowledge.